The Effect of Health and Health Shocks on Hours Worked - Oguzoglu, U; Mavromaras, K; Cai, L (My University, 2008)
We investigate the impact of health on working hours in recognition of the fact that leaving the labour market due to persistently low levels of health stock or due to new health shocks, is only one of the possibilities open to employees. We use the first six waves of the HILDA survey to estimate the joint effect of health status and health shocks on working hours using a dynamic random effects Tobit model of working hours to account for zero working hours. We follow Heckman (1981) and approximate the unknown initial conditions with a static equation that utilizes information from the first wave of the data. Predicted individual health stocks are used to ameliorate the possible effects of measurement error and endogeneity. We conclude that overall lower health status results in lower working hours and that health shocks lead to further reductions in working hours when they occur. Estimation results show that the model performs well in separating the time-persistent effect of health stock (health status) and the potentially more transient health shocks on working hours.
IZA Discussion Paper
IZA Discussion Papers
Keywords: Employment; Employment -- Hours; Health; Labour market; Employment and unemployment